Policy uncertainty, investment, and the cost of capital - Drobetz, Wolfgang; El Ghoul, Sadok; Guedhami, Omrane; Janzen, Malte (Journal of Financial Stability, 2018)
We examine the effect of economic policy uncertainty on the relation between investment and the cost of capital. Using the news-based index developed by Baker et al. (2016) for twenty-one countries, we find that the strength of the negative relation between investment and the cost of capital decreases during times of high economic policy uncertainty. An increase in policy uncertainty reduces the sensitivity of investment to the cost of capital most for firms operating in industries that depend strongly on government subsidies and government consumption as well as in countries with high state ownership. Consistent with the price informativeness channel, we find that an increase in policy uncertainty reduces the investment-cost of capital sensitivity for firms from more opaque countries, firms with low analyst coverage, firms with no credit rating, and small firms. We conclude that economic policy uncertainty distorts the fundamental relation between investment and the cost of capital.